2022
DOI: 10.2478/cipms-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 infection during pregnancy

Abstract: Parvovirus B19 (B19V) is a widespread pathogen causing infection that occurs mostly in children. Even though infection of B19V is mainly asymptomatic, it can bring about a few conditions that may require medical intervention, including erythema infectiosum (fifth disease), slapped cheek syndrome, papular-purpuric gloves and socks syndrome (PPGSS), as well as other disorders related to the hematological system. Despite the fact that the most common route of transmission is through the respiratory system, B19V c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(98 reference statements)
0
1
2
Order By: Relevance
“…The result of this study was also higher to that reported by another study conducted in Sudan by [23], who reported a seropositivity rate of (41%). The result of this study is also higher than the result of the study reported in Libya by [16] who reported a seropositivity rate of 5%. However the result of this study was lower than the result of a study conducted in Italy by [24] who reported a seropositivity rate of (96.3%).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The result of this study was also higher to that reported by another study conducted in Sudan by [23], who reported a seropositivity rate of (41%). The result of this study is also higher than the result of the study reported in Libya by [16] who reported a seropositivity rate of 5%. However the result of this study was lower than the result of a study conducted in Italy by [24] who reported a seropositivity rate of (96.3%).…”
Section: Discussioncontrasting
confidence: 84%
“…The findings of this study was also higher than the report of the study conducted by [16] on Parvovirus B19 infection in pregnancy who reported that the spontaneous loss rate of fetuses affected with Parvovirus B19 in their first trimester was (13.0%) and higher than the spontaneous loss rate of fetuses affected with Parvovirus B19 in their second trimester (0.5%) [16]. the difference may be due to the different diagnostic techniques demographic and geographical variation, type of samples and the population investigated.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation